Analysis of the complete plastomes of three species of Membranoptera (Ceramiales, Rhodophyta) from Pacific North America. Issue 1 (2nd November 2016) - Hughey, Jeffery R.; Hommersand, Max H.; Gabrielson, Paul W.; Miller, Kathy Ann; Fuller, Timothy
Abstract : Next generation sequence data were generated and used to assemble the complete plastomes of the holotype of Membranoptera weeksiae, the neotype (designated here) of M. tenuis, and a specimen examined by Kylin in making the new combination M. platyphylla . The three plastomes were similar in gene content and length and showed high gene synteny to Calliarthron, Grateloupia, Sporolithon, and Vertebrata . Sequence variation in the plastome coding regions were 0.89% between M. weeksiae and M. tenuis, 5.14% between M. weeksiae and M. platyphylla, and 5.18% between M. tenuis and M. platyphylla . We were unable to decipher the complete mitogenomes of the three species due to low coverage and structural problems; however, we assembled and analyzed, the cytochrome oxidase I, II, and III loci and found that M. weeksiae and M. tenuis differed in sequence by 1.3%, M. weeksiae and M. platyphylla by 8.4%, and M. tenuis and M. platyphylla by 8.1%. Evaluation of standard marker genes indicated that sequences from the rbc L, RuBisCO spacer, and CO1 genes closely approximated the pair‐wise genetic distances observed between the plastomes of the three species of Membranoptera . A phylogenetic tree based on rbc L sequences showed that M. tenuis and M. weeksiae were sister taxa. Short rbc L sequences were obtained from type specimens of M. dimorpha, M. multiramosa, and M. edentata and confirmed their conspecificity with M. platyphylla . The data support the recognition of three species of Membranoptera occurring south of Alaska: M. platyphylla, M. tenuis, and M. weeksiae .